Introduce Mathematical Concepts for Early Childhood: Inhibiting and Supporting Factors through Play in Children’s Cognitive Stimulation - Sufa, Feri Faila; Gunarhadi; Akhyar, Muhammad; Munawir (International Journal of Psychosocial Rehabilitation, 2020)
Mathematical ability is essential in everyday life and is beneficial in all fields of life. Introducing the concept of mathematics from an early age is very important so that children have readiness in facing mathematics in subsequent education. This article aims to describe the inhibiting and supporting factors of learning mathematical concepts at an early age through playing at PAUD institutions in Solo Raya, Central Java Province of Indonesia. The data collection techniques used are observation and interviews analyzed through a qualitative approach. The results obtained from this study are that mathematical concepts can build children’s cognition to reason, think creatively through imaginative play. By playing imagination, children can explore the media used to find mathematical concepts, both in introducing the idea of numbers, geometry concepts and patterns.